195 3D Genome Structure and Epigenetic Transcription Regulation in Pediatric High-Grade Glioma. (1st April 2022) - Saratsis, Amanda M.; Huang, Tina; Wang, Juan; Hu, Ye; Piunti, Andrea; Bartom, Elizabeth; Shilatifard, Ali; Yue, Feng
Abstract : INTRODUCTION: Pediatric high-grade gliomas (pHGGs), including glioblastoma multiforme (GBM) and diffuse intrinsic pontine glioma (DIPG), are highly morbid brain tumors. Up to 80% of DIPGs harbor a somatic missense mutation in genes encoding Histone H3. To investigate whether the H3K27M mutant protein is associated with distinct chromatin structure affecting transcription regulation, we generated the first high-resolution Hi-C and ATAC-Seq maps of pHGG cell lines, and integrated these with tissue and cell genomic data. METHODS: We sequenced patient-derived cell lines (DIPG n = 6, GBM n = 3, normal n = 2) and frozen tissue specimens (DIPG n = 1, normal brainstem n = 1). Analyses included cell line RNA-Seq, ChIP-Seq (H3K27ac, H3K27me3, H3K27M) and genome-wide chromatin conformation capture (Hi-C), as well as tissue ATAC-Seq. Publicly available pediatric glioma tissue ChIP-Seq data was integrated with cell data. RESULTS: We identified tumor-specific enhancers and regulatory networks for known oncogenes in DIPG and GBM. In DIPG, FOX, SOX, and STAT families were among top H3K27Ac enriched motifs. Significant differences in Topologically Associating Domains (TADs) and DNA looping were observed at OLIG2 and MYCN in H3K27M mutant DIPG, relative to wild-type GBM and normal cells. Pharmacologic treatment targeting H3K27Ac (BET and Bromodomain inhibition) altered these 3D structures. Functional analysis of differentially enriched enhancers in DIPG implicated SOX2, SUZ12, and TRIM24 as top activated upstream regulators. Distinct genomic structural variations leading to enhancer hijacking and gene co-amplification were identified at A2M, JAG2, and FLRT1. CONCLUSION: We show genome structural variations enhancer-promoter interactions that impact gene expression in pHGG in the presence and absence of the H3K27M mutation. Our results imply that tridimensional genome alterations may play a critical role in the pHGG epigenetic landscape and thereby contribute to pediatric gliomagenesis. Further studies examining the impact of the alterations are therefore underway.